Validitas LKS berbasis problem solving bermuatan strategy formation of critical thinking pada materi dinamika rotasi dan elastisitas fisika SMA/MA - Melani Alvino; Yenni Darvina; Wahyuni Satria Dewi; Amali Putra (Universitas Negeri Padang, 2020)
In improving the quality of life in this 21st century era, one of the areas that is highly considered is education. There are three aspects that become the demands of the education sector today, namely character, competence, and literacy. in the competency section there is a skill called the 4C skill. 4C skills consist of communication skills, critical thinking skills, collaboration skills, and creativity skills. 4C skills must be possessed by students in the learning process. One means of applying 4C skills is through teaching materials, one of them is Student Worksheets. In this research, a worksheet based on problem solving with strategy formation of critical thinking on the dynamics of rotation and elasticity has been produced. This is a R&D research, it is research and development that is based on Sugiyono theory in his book and there is a kind of test that is validity to the product. The result of validity tests from three validators based on six components are 85.56%, 77.08%, 81.82%, 83.3%, 85.0%, and 80.0% with the overall average are 82.13% it can be categorize as very valid.